Advances in Cryptology - ASIACRYPT 2013 19th International Conference on the Theory and Application of Cryptology and Information Security, Bengaluru, India, December 1-5, 2013, Proceedings, Part I - Sako, Kazue; Sarkar, Palash; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The two-volume set LNCS 8269 and 8270 constitutes the refereed proceedings of the 19th International Conference on the Theory and Application of Cryptology and Information, Asiacrypt 2013, held in Bengaluru, India, in December 2013. The 54 revised full papers presented were carefully selected from 269 submissions. They are organized in topical sections named: zero-knowledge, algebraic cryptography, theoretical cryptography, protocols, symmetric key cryptanalysis, symmetric key cryptology: schemes and analysis, side-channel cryptanalysis, message authentication codes, signatures, cryptography based upon physical assumptions, multi-party computation, cryptographic primitives, analysis, cryptanalysis and passwords, leakage-resilient cryptography, two-party computation, hash functions.
Message Authentication Codes -- Signatures -- Cryptography Based Upon Physical Assumptions -- Multi-Party Computation -- Cryptographic Primitives -- Analysis, Cryptanalysis and Passwords -- Leakage-Resilient Cryptography -- Two-Party Computation -- Hash Functions.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Mathematics; Computer Science; Data Encryption; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Discrete Mathematics in Computer Science; Systems and Data Security; Applications of Mathematics